PENINGKATAN KUALITAS JASA PELAYANAN TERHADAP KEPUASAN PASIEN PUSKESMAS (Studi Kasus Puskesmas Petaling Mendo Barat) - Nurhayati; Zamhari; Tri Setyo Mulyani, Hendarti (Jurnal Progresif Manajemen Bisnis, 2019)
This thesis was written and compiled by Nurhayati (230150065), entitled: "Strategies for Improving Service Quality Based on Analysis of Health Center Patient Satisfaction (Case Study in Petaling Mendo West Health Center)". The purpose of this study was to determine the effect of direct evidence, reliability, assurance, responsiveness and empathy for patient satisfaction, both simultaneously and partially. This research was conducted in March 2019 until June 2019. The theories used in this study are Management theory, Marketing, Strategy Management theory, Marketing Management, Service Quality Theory and Consumer Satisfaction Theory. The method used in this study is descriptive with a quantitative approach with the aim to find the relationship between independent variables and dependent variables using a statistical formula that examines the relationship of the effect of direct evidence, reliability, assurance, responsiveness and empathy to patient satisfaction at Mendo Barat Health Center. While the statistical formula used to test the hypothesis is Multiple Linear Regression Analysis. The sample in this study amounted to 100 people. The results of the study revealed that: (1) there was a significant effect on direct evidence, reliability, assurance, responsiveness and empathy for the satisfaction of Mendo Barat Community Health Center patients as evidenced by the F count (64.69)> Ftable (2.31). (2) The results of the study also prove that there is a significant influence between direct evidence variables on patient satisfaction. This is evidenced by the value of t-count> t-table (2.174> 1.98447). (3) The results of the study indicate that there is a significant influence between the variables of reliability on patient satisfaction. This is evidenced by the value of t count (3.802)> t table (1.98447). (4) The results of the study showed a significant effect between the guarantee variables on patient satisfaction. This is evidenced by thitung (9,080)> t table (1,98447). (5) The results of the study indicate that there is a significant influence between the variables of responsiveness to patient satisfaction. This is evidenced by the value of tcount (4,963)> t table (1,98447). And (6) the results of the study showed a significant effect between the variables of empathy on patient satisfaction. This is evidenced by tcount (2,095)> t table (1,98447).